Bismuth-based bromide ion adsorbent material as well as preparation method and application thereof
By doping PPy on SrBiO2Br to prepare SrBiO2Br-PPy adsorbent, the problems of low efficiency and high energy consumption in bromine extraction from seawater were solved, efficient and environmentally friendly bromide ion adsorption and separation were achieved, and the scope of application was expanded.
Patent Information
- Application Number
- CN202510790451.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-10-03
AI Technical Summary
Existing methods for extracting bromine from seawater have high energy consumption, large equipment investment, low safety, and low bromine extraction efficiency. Traditional BiOBr adsorbent materials are complex to operate and highly toxic, making it difficult to meet industrial application needs.
By doping polypyrrole (PPy) on irregular micron-shaped SrBiO2Br, SrBiO2Br-PPy adsorbent material was prepared to increase ion capture sites and improve ion transfer rate, and the electrochemical ion exchange technology was combined to achieve efficient adsorption and separation of bromide ions.
It improves the adsorption performance of bromide ions and the efficiency of bromine extraction, reduces energy consumption, expands the application field, has good material stability, is simple to operate, is non-toxic and harmless, and is suitable for industrial applications.
Smart Images

Figure CN120733706A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adsorbent materials, and in particular relates to a bismuth-based bromide ion adsorbent material, a preparation method thereof, and an application thereof. Background Art
[0002] Bromine is one of the important chemical raw materials and a major branch of the marine chemical industry. The inorganic bromides, bromates and bromine-containing organic compounds derived from it have special value in the national economy and scientific and technological development. Bromine mainly exists in the form of ions in salt water systems such as seawater, salt lake brine and underground brine. - The concentration in seawater is 40-65 mg·L -1 The storage capacity can reach 100 trillion tons, and it is known as the "ocean element". my country's bromine supply has long been in short supply and relies on large quantities of imports each year. Therefore, seawater bromine extraction has broad development prospects.
[0003] Air extraction and steam distillation are currently the primary methods for extracting bromine from seawater. Both methods suffer from drawbacks such as high energy consumption, large equipment investment, large floor space requirements, and low safety. However, no mature new methods have yet emerged to replace them. With modern industry's technological demands for sustainable development goals, such as reducing costs, equipment size, energy consumption, and waste generation, exploring new extraction methods is a growing trend in industrial bromine production. Bromine extraction using adsorbents can be performed directly from seawater, eliminating the acidification and oxidation processes. These methods offer low energy consumption, minimal investment, and are environmentally friendly, making them a hot topic in seawater bromine extraction research. However, the performance of bromine extraction adsorbents, such as extraction efficiency and adsorption capacity, still needs to be improved to meet practical industrial applications.
[0004] Chinese invention patent document CN117845270A discloses a BiOBr / PPy-Br composite membrane electrode for electrically controlled bromine extraction from concentrated seawater and its preparation method. The method uses a hydrothermal method to prepare bismuth oxybromide. An intercalation reaction is carried out under the action of formamide, and pyrrole monomers are intercalated into the interlayers of bismuth oxybromide nanosheets through an in-situ chemical oxidation method to form a bismuth oxybromide / bromide ion imprinted polypyrrole electroactive material. The BiOBr doping process requires formamide for the intercalation reaction, which is highly toxic and increases the difficulty of experimental operation. The present invention prepares bismuth oxybromide through a simple hydrothermal reaction and only requires one step of grinding and calcination to obtain SrBiO2Br. Compared with a single BiOBr adsorbent material, SrBiO2Br has superior adsorption performance. Pyrrole is then oxidized with FeCl3·6H2O to form polypyrrole, thereby obtaining a bismuth-based bromide ion adsorbent material. The material is simple to operate and non-toxic. Summary of the Invention
[0005] The purpose of the present invention is to provide a bismuth-based bromide ion adsorbent and its preparation method and application, by doping PPy to increase the ion capture site, improve the ion transfer rate of SrBiO2Br-PPy adsorbent material, thereby improving the SrBiO2Br to Br - It can directly extract bromine by combining electrochemical ion exchange technology to solve the problem of low bromine extraction rate in seawater.
[0006] In order to solve the above problems, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a bismuth-based bromide ion adsorbent material, comprising irregular micron-plate-shaped SrBiO2Br and a modified layer of polypyrrole PPy, wherein the modified layer PPy is uniformly attached to the irregular micron-plate-shaped SrBiO2Br; the molar ratio of the micron-plate-shaped SrBiO2Br to the modified layer PPy is 0.5 to 1.5:1.
[0007] Preferably, the molar ratio of the micron plate-shaped SrBiO2Br to the modified layer PPy is 1:1.
[0008] Preferably, the micron-plate-shaped SrBiO2Br has a width of 1 to 5 μm and a thickness of 200 to 500 nm.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned bismuth-based bromide ion adsorbent material, comprising the following steps: S1. Dissolve Bi(NO₃)₃·5H₂O in ethanol, then dissolve KBr in deionized water and add the solution dropwise. A hydrothermal reaction is then performed, followed by centrifugation and drying to obtain BiOBr. Finally, SrCO₃ and BiOBr are mixed, ground, and calcined to obtain SrBiO₂Br. S2. SrBiO2Br and pyrrole (Py) monomers were dispersed in deionized water. FeCl3·6H2O was then evenly added. The mixture was reacted in an ice bath. The mixture was then centrifuged and dried to obtain the SrBiO2Br-PPy adsorbent material.
[0010] Preferably, in step S1, the molar ratio of Bi(NO3)3·5H2O to KBr is 1:1, the hydrothermal reaction temperature is 140-180°C, and the hydrothermal reaction time is 16-20 hours; the drying temperature is 60-80°C, and the drying time is 6-12 hours; the molar ratio of SrCO3 to BiOBr is 1:1, the calcination temperature is 600-800°C, and the calcination time is 3-5 hours.
[0011] Preferably, in step S2, the molar ratio of SrBiO2Br, Py and FeCl3·6H2O is 0.5-1.5:1:0.3-0.6; the ice bath temperature is -1-0°C, and the ice bath reaction time is 8-12 hours; the drying temperature is 60-80°C, and the drying time is 6-12 hours.
[0012] In a third aspect, the present invention prepares bromide ion separation electrode materials using the above-mentioned SrBiO2Br-PPy adsorbent material, and applies it to the field of bromine extraction from seawater.
[0013] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: (1) The bismuth-based bromide ion adsorbent material provided by the present invention can not only increase the ion capture sites of the adsorbent material by doping the modified layer PPy on the irregular micron plate-shaped SrBiO2Br, but also improve the ion transfer rate of the SrBiO2Br-PPy adsorbent material. At the same time, the synergistic redox effect of PPy and SrBiO2Br strengthens the potential driving force on the adsorbent material, thereby improving the SrBiO2Br-PPy adsorbent material's Br absorption. - adsorption performance.
[0014] (2) The stable chemical structure of SrBiO2Br and the flexible skeleton of PPy in the bismuth-based bromide ion adsorbent material provided by the present invention can alleviate the volume expansion of SrBiO2Br during the adsorption-desorption cycle, prolong the material life, and make the SrBiO2Br-PPy adsorbent material have excellent stability under the oxidation and reduction voltages required for bromine extraction. Experimental Example 8 conducted 10 cycles of capture / release experiments on the SrBiO2Br-PPy adsorbent material. The capture capacity retention efficiency of the SrBiO2Br-PPy adsorbent material remained almost unchanged in the 10 repeated cycles. - The release rate also remained above 60% in each cycle, indicating that the SrBiO2Br-PPy adsorbent material has good stability.
[0015] (3) The application of the bismuth-based bromide ion adsorbent material provided by the present invention is to realize the adsorption and separation of bromide ions in seawater by using the electrochemical ion exchange technology in conjunction with the SrBiO2Br-PPy adsorbent material under the synergistic effect of electrochemical potential control. In Example 5, the adsorption of bromide ions in seawater by the SrBiO2Br-PPy adsorbent material was measured under the same conditions. - The adsorption capacity is large, and the adsorption rate can reach 85.3%, which is 1.75 times that of the single SrBiO2Br adsorbent material. It does not require the acidification and oxidation process of traditional bromine extraction. Compared with existing technologies, the bromine extraction efficiency is higher, the energy consumption is reduced, and it is more green and environmentally friendly. At the same time, it expands the application field of bismuth-based adsorbent materials.
[0016] (4) The preparation method of the bismuth-based bromide ion adsorbent material provided by the present invention is simple, has mild reaction conditions and is pollution-free, and has broad industrial application prospects in the field of green and efficient bromine extraction from seawater. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SEM images of the samples synthesized in Example 3 and Comparative Example 1 are shown; Figure 2 The XRD spectra of the samples synthesized in Example 3 and Comparative Example 1 are shown; Figure 3 FTIR spectra of the samples synthesized in Example 3 and Comparative Example 1; Figure 4 The adsorbent material prepared in Example 3 is subjected to Br at different potentials. - Adsorption performance; Figure 5 Example 3 shows the effect of pH on the capture of Br by adsorbent materials. - Impact diagrams of capabilities; Figure 6 Capacity retention efficiency and release rate graph of the adsorbent material prepared for Example 3. DETAILED DESCRIPTION
[0018] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or the conditions recommended by the manufacturer. Those whose reagents or instruments are not specified by the manufacturer are conventional products that can be purchased commercially.
[0019] The numerical values in the synthetic samples in the examples and comparative examples all represent the content of the substances. For example, 1.5SrBiO2Br-PPy means that the molar ratio of SrBiO2Br to PPy is 1.5:1, and so on. Example 1
[0020] (1) 5.0 mmol of Bi(NO3)3·5H2O was dissolved in 25 mL of ethanol, recorded as solution A, and 5.0 mmol of KBr was stirred and dissolved in 10 mL of deionized water, recorded as solution B. Solution B was added dropwise to solution A and hydrothermally reacted at 140°C for 18 h. The mixture was then centrifuged and dried at 60°C for 12 h to obtain BiOBr. Finally, 2.0 mmol of SrCO3 and 2.0 mmol of BiOBr were mixed and ground, and calcined at 800°C for 5 h to obtain a micron-plate-shaped SrBiO2Br adsorbent material.
[0021] (2) 0.5 mol of SrBiO2Br and 1.0 mol of pyrrole monomer were dispersed in deionized water and placed in an ice bath at -1°C under continuous stirring. 0.3 mol of FeCl3·6H2O was then added and the mixture was reacted in an ice bath for 8 h. Finally, the mixture was centrifuged and dried at 80°C for 8 h to obtain a micron-plate-shaped 0.5SrBiO2Br-PPy adsorbent material. Example 2
[0022] (1) 5.0 mmol of Bi(NO3)3·5H2O was dissolved in 25 mL of ethanol, recorded as solution A, and 5.0 mmol of KBr was stirred and dissolved in 10 mL of deionized water, recorded as solution B. Solution B was added dropwise to solution A and hydrothermally reacted at 150°C for 17 h; then centrifuged and dried at 80°C for 10 h to obtain BiOBr; finally, 2.0 mmol of SrCO3 and 2.0 mmol of BiOBr were mixed and ground, and calcined at 600°C for 4 h to obtain a micron-plate-shaped SrBiO2Br adsorbent material.
[0023] (2) 0.8 mol of SrBiO2Br and 1.0 mol of pyrrole monomer were dispersed in deionized water and placed in an ice bath at 0°C under continuous stirring. 0.5 mol of FeCl3·6H2O was then added and the mixture was reacted in an ice bath for 10 h. Finally, the mixture was centrifuged and dried at 70°C for 10 h to obtain a micron-plate-shaped 0.8SrBiO2Br-PPy adsorbent material. Example 3
[0024] (1) 5.0 mmol of Bi(NO3)3·5H2O was dissolved in 25 mL of ethanol, recorded as solution A, and 5.0 mmol of KBr was stirred and dissolved in 10 mL of deionized water, recorded as solution B. Solution B was added dropwise to solution A and hydrothermally reacted at 160°C for 20 h. The mixture was then centrifuged and dried at 80°C for 6 h to obtain BiOBr. Finally, 2.0 mmol of SrCO3 and 2.0 mmol of BiOBr were mixed and ground, and calcined at 700°C for 4 h to obtain a micron-plate-shaped SrBiO2Br adsorbent material.
[0025] (2) 1.0 mol of SrBiO2Br and 1.0 mol of pyrrole monomer were dispersed in deionized water and placed in an ice bath at 0°C under continuous stirring. 0.4 mol of FeCl3·6H2O was then added and the mixture was reacted in an ice bath for 12 h. Finally, the mixture was centrifuged and dried at 60°C for 12 h to obtain a micron-plate-shaped SrBiO2Br-PPy adsorbent material. Example 4
[0026] (1) 5.0 mmol of Bi(NO3)3·5H2O was dissolved in 25 mL of ethanol, recorded as solution A, and 5.0 mmol of KBr was stirred and dissolved in 10 mL of deionized water, recorded as solution B. Solution B was added dropwise to solution A and hydrothermally reacted at 180°C for 16 h; then centrifuged and dried at 70°C for 8 h to obtain BiOBr; finally, 2.0 mmol of SrCO3 and 2.0 mmol of BiOBr were mixed and ground, and calcined at 800°C for 3 h to obtain a micron-plate-shaped SrBiO2Br adsorbent material.
[0027] (2) 1.2 mol of SrBiO2Br and 1.0 mol of pyrrole monomer were dispersed in deionized water and placed in an ice bath at -1°C under continuous stirring. 0.6 mol of FeCl3·6H2O was then added and the mixture was reacted in an ice bath for 9 h. Finally, the mixture was centrifuged and dried at 80°C for 6 h to obtain a micron-plate-shaped 1.2SrBiO2Br-PPy adsorbent material. Example 5
[0028] (1) 5.0 mmol of Bi(NO3)3·5H2O was dissolved in 25 mL of ethanol, recorded as solution A, and 5.0 mmol of KBr was stirred and dissolved in 10 mL of deionized water, recorded as solution B. Solution B was added dropwise to solution A and hydrothermally reacted at 170°C for 17 h; then centrifuged and dried at 60°C for 10 h to obtain BiOBr; finally, 2.0 mmol of SrCO3 and 2.0 mmol of BiOBr were mixed and ground, and calcined at 700°C for 5 h to obtain a micron-plate-shaped SrBiO2Br adsorbent material.
[0029] (2) 1.5 mol of SrBiO2Br and 1.0 mol of pyrrole monomer were dispersed in deionized water and placed in an ice bath at 0°C under continuous stirring. 0.5 mol of FeCl3·6H2O was then added and the mixture was reacted in an ice bath for 11 h. Finally, the mixture was centrifuged and dried at 75°C for 11 h to obtain a micron-plate-shaped 1.5SrBiO2Br-PPy adsorbent material. Example 6
[0030] The samples synthesized in Examples 1-5 were mixed with different proportions of SrBiO2Br-PPy adsorbent material, carbon black (CB) and polytetrafluoroethylene (PVDF) in a mass ratio of 8:1:1, fully ground, and then stirred with an appropriate amount of NMP solvent for 2 hours; finally, they were evenly coated on a pretreated carbon plate and dried in a vacuum oven at 60°C for 12 hours to obtain SrBiO2Br-PPy electrode materials with different proportions. Comparative Example 1
[0031] 5.0 mmol of Bi(NO3)3·5H2O was dissolved in 25 mL of ethanol, recorded as solution A, and 5.0 mmol of KBr was stirred and dissolved in 10 mL of deionized water, recorded as solution B. Solution B was added dropwise to solution A and hydrothermally reacted at 160°C for 20 hours; then centrifuged and dried at 80°C for 6 hours to obtain BiOBr; finally, 2.0 mmol of SrCO3 and 2.0 mmol of BiOBr were mixed and ground, and calcined at 700°C for 4 hours to obtain a micron-plate-shaped SrBiO2Br adsorbent material. Comparative Example 2
[0032] The sample synthesized in Comparative Example 1 was mixed with SrBiO2Br adsorbent material, carbon black (CB) and polytetrafluoroethylene (PVDF) in a mass ratio of 8:1:1, fully ground, and then stirred with an appropriate amount of NMP solvent for more than 2 hours; finally, it was evenly coated on a pretreated carbon plate and dried in a vacuum oven at 60°C for 12 hours to obtain a SrBiO2Br electrode material. Experimental Example 1
[0033] Figure 1 The morphology of the samples obtained in Example 3 and Comparative Example 1 is shown in FIG. Figure 1 As shown in a, SrBiO2Br is composed of stacked plate structures with a width of 1 to 5 μm and a thickness of 200 to 500 nm; Figure 1 b is the SEM image of the sample synthesized in Example 3. Compared with SrBiO2Br, the morphology of SrBiO2Br-PPy still maintains a plate-like structure. This is because the mild oxidative polymerization process of PPy and the appropriate modification of PPy have no significant effect on the morphology of SrBiO2Br. Compared with Comparative Example 1, Example 3 shows that the modification of PPy not only increases the ion capture sites of the adsorbent material, but also improves the conductive properties of the adsorbent material and enhances the ion transfer rate of the SrBiO2Br-PPy adsorbent material, thereby improving the adsorbent's absorption of Br. - adsorption performance. Experimental Example 2
[0034] Figure 2The XRD spectra of the samples prepared in Example 3 and Comparative Example 1 were analyzed. After solid-state reaction at 700°C, the diffraction peak of SrCO3 disappeared, and the low-crystallinity SrBiO2Br peak was formed. The diffraction peaks of SrBiO2Br at 16.80, 30.42, and 44.90 were well matched with the diffraction peaks of SrBiO2Br (PDF#97509), and no other impurity peaks were observed, indicating that the SrBiO2Br material was successfully prepared and had high purity and high crystallinity. In addition, due to the uniform dispersion and low content of PPy on SrBiO2Br, no PPy diffraction peak was observed in the SrBiO2Br-PPy adsorbent material. This shows that PPy is only present on the surface of SrBiO2Br and does not affect the original crystal structure of SrBiO2Br. Experimental Example 3
[0035] Figure 3 The FTIR images of the samples synthesized in Example 3 and Comparative Example 1 were analyzed. The SrBiO2Br adsorbent material had a -1 A characteristic peak was observed at 1036 cm, which was attributed to the symmetrical stretching vibration of Bi-O. -1 The peak at 1498 cm is attributed to the in-plane deformation vibration of the NH bond of PPy. -1 The energy band at indicates that PPy is in a doped state, which is conducive to charge transfer; the characteristic peaks of the above two samples appear simultaneously in the FTIR spectrum of the SrBiO2Br-PPy adsorbent material, which also proves that the SrBiO2Br-PPy adsorbent material is successfully synthesized. Experimental Example 4
[0036] The adsorbent materials prepared in Example 6 and Comparative Example 2 were tested for their Br - The adsorption performance test is shown in Table 1 below. By comparing the adsorption capacity of SrBiO2Br-PPy and SrBiO2Br at different ratios, 6.0 mg of adsorbent material was used to adsorb 8 L of 100 mg·L -1 Br - The adsorption test of the solution was carried out for 30 min. As can be seen from Table 1, the SrBiO2Br-PPy adsorbent material has a strong affinity for Br - The adsorption capacity is the highest. Compared with pure SrBiO2Br, the adsorption capacity of SrBiO2Br-PPy adsorbent material is much higher than that of SrBiO2Br, which is 1.67 times that of pure SrBiO2Br. This shows that the capture ability of SrBiO2Br-PPy adsorbent material is higher than that of pure SrBiO2Br and PPy. This further shows that doping PPy can not only increase the ion capture sites, but also improve the ion transfer rate of the adsorbent material. More Br- The reason for the entry into the SrBiO2Br-PPy adsorbent material is due to the synergistic redox effect of PPy and SrBiO2Br, which enhances the potential driving force on the adsorbent material.
[0037] Experimental Example 5
[0038] Table 2 shows the adsorbent materials prepared in Example 6 and Comparative Example 2 for Br - The adsorption and extraction effect of 10 mg of adsorbent material was tested at 1.2 V and pH = 7 for 8 L of 105 mg·L -1 Br - The adsorption reaction of the solution was carried out for 30 minutes. It can be seen from Table 2 that the SrBiO2Br adsorbent material has a good effect on Br - The adsorption of Br is limited, with an adsorption rate of 48.8%. - The adsorption capacity of PPy is large, and the adsorption rate can reach 85.3%, which is 1.75 times that of the single SrBiO2Br adsorbent material. This further shows that doping PPy can not only increase the adsorption of Br - The capture sites can also increase the ion transfer rate of the adsorbent material.
[0039] Experimental Example 6
[0040] The choice of potential has an important influence on the bromine extraction of adsorbents. If the potential is too low, the adsorption reaction rate will be slow. If the potential is too high, Cl - The oxidation side reaction and water electrolysis affect the current efficiency of subsequent reactions; Figure 4 The SrBiO2Br-PPy pair containing 100mg·L at different potentials was tested. -1 Br - The adsorption properties of the solution are determined by Figure 4 It can be seen that at 1.2V, SrBiO2Br-PPy is - The adsorption capacity and rate are both optimal. The adsorption capacity can reach 128.45 mg / g within 30 minutes. After 30 minutes of adsorption reaction, the adsorption capacity does not change much, indicating that 1.2 V is the optimal adsorption potential for bromine extraction of the adsorbent material. Experimental Example 7
[0041] In order to study the effect of pH value on the capture capacity of adsorbent materials, 4.0 mg of adsorbent was used to collect 6 L of 100 mg·L -1 Br - The solution adsorption test was conducted for 30 min. Figure 5As shown in the figure, the SrBiO2Br-PPy adsorbent material has a wide pH range for Br - It has good capture ability and its adsorption capacity is maintained at 100 mg g -1 In the pH range of 2~3, the capture capacity of SrBiO2Br-PPy adsorbent material is higher, which may be due to the higher acid concentration in the solution, which increases the conductivity of the solution and is conducive to the absorption of Br. - With the increase of pH, due to the presence of a large number of Br - Competitive OH - , SrBiO2Br-PPy adsorbent material for Br - The capture capacity is on a downward trend. Experimental Example 8
[0042] Stability is crucial for the practical application of adsorbent bromine extraction. In order to explore the stability of SrBiO2Br-PPy adsorbent material, 6.0 mg of adsorbent material was used to precipitate 8 L of 100 mg·L -1 Br - The solution was subjected to adsorption test for 30 min, and then 10 cycles of capture / release experiments were performed, e.g. Figure 6 As shown in Figure 2, the capture capacity retention efficiency of the SrBiO2Br-PPy adsorbent material remained almost unchanged during 10 repeated cycles. - The release rate also remained above 60% in each cycle, demonstrating the excellent stability of the adsorbent material under appropriate oxidation and reduction voltages.
Claims
1. A bismuth-based bromide ion adsorbent material, characterized in that: The adsorbent comprises irregular micron-plate-shaped SrBiO2Br and a modified layer of polypyrrole PPy, wherein the modified layer PPy is uniformly attached to the irregular micron-plate-shaped SrBiO2Br; and the molar ratio of the micron-plate-shaped SrBiO2Br to the modified layer PPy is 0.5-1.5:
1.
2. The bismuth-based bromide ion adsorbent material according to claim 1, characterized in that: The molar ratio of the micron plate-shaped SrBiO2Br to the modified layer PPy is 1:
1.
3. The bismuth-based bromide ion adsorbent material according to claim 1, characterized in that: The micron-plate-shaped SrBiO2Br has a width of 1 to 5 μm and a thickness of 200 to 500 nm.
4. A method for preparing the bismuth-based bromide ion adsorbent material according to claim 1, characterized in that: The steps include: S1. Dissolve Bi(NO₃)₃·5H₂O in ethanol, then dissolve KBr in deionized water and add the solution dropwise. A hydrothermal reaction is then performed, followed by centrifugation and drying to obtain BiOBr. Finally, SrCO₃ and BiOBr are mixed, ground, and calcined to obtain SrBiO₂Br. S2. SrBiO2Br and pyrrole monomers were dispersed in deionized water, and FeCl3·6H2O was added. The mixture was reacted in an ice bath, and finally centrifuged and dried to obtain a bismuth-based bromide ion adsorbent material.
5. The method for preparing a bismuth-based bromide ion adsorbent material according to claim 4, characterized in that: In step S1, the molar ratio of Bi(NO3)3·5H2O to KBr is 1:1, the hydrothermal reaction temperature is 140-180°C, and the hydrothermal reaction time is 16-20 hours; the drying temperature is 60-80°C, and the drying time is 6-12 hours; the molar ratio of SrCO3 to BiOBr is 1:1, the calcination temperature is 600-800°C, and the calcination time is 3-5 hours.
6. The method for preparing a bismuth-based bromide ion adsorbent material according to claim 4, wherein: In step S2, the molar ratio of SrBiO2Br, pyrrole monomer and FeCl3·6H2O is 0.5-1.5:1:0.3-0.6; the ice bath reaction temperature is -1-0°C, and the ice bath reaction time is 8-12 hours; the drying temperature is 60-80°C, and the drying time is 6-12 hours.
7. A use of the bismuth-based bromide ion adsorbent material according to claim 1, characterized in that: The bismuth-based bromide ion adsorbent material is used to prepare a bromide ion separation electrode material, which is applied in the field of bromine extraction from seawater.
Citation Information
Patent Citations
BiOBr / PPy-Br composite membrane electrode for electric control bromine extraction of concentrated seawater and preparation method of BiOBr / PPy-Br composite membrane electrode
CN117845270A